2003
DOI: 10.2527/2003.8171706x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping a quantitative trait locus affecting ovulation rate in swine on chromosome 81

Abstract: Ovulation rate is an integral component of litter size in swine, but is difficult to directly select for in commercial swine production. Because a QTL has been detected for ovulation rate at the terminal end of chromosome 8p, genetic markers for this QTL would enable direct selection for ovulation rate in both males and females. Eleven genes from human chromosome 4p16-p15, as well as one physiological candidate gene, were genetically mapped in the pig. Large insert swine genomic libraries were screened, clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Braunschweig et al (2001) refined the genetic map by the use of 29 markers and confirmed the QTL at the centromere region of SSC8. Campbell et al (2003) narrowed the region at the telomeric end of the short arm on SSC8 using gene and microsatellite markers within the first 27 cM and confirmed and narrowed the QTL found by Rohrer et al (1999). Additional significant QTL for ovulation rate were found on SSC9 (Cassady et al, 2001), SSC13 and SSC15 (Rathje et al, 1997).…”
Section: Ovulation Ratesupporting
confidence: 53%
“…Braunschweig et al (2001) refined the genetic map by the use of 29 markers and confirmed the QTL at the centromere region of SSC8. Campbell et al (2003) narrowed the region at the telomeric end of the short arm on SSC8 using gene and microsatellite markers within the first 27 cM and confirmed and narrowed the QTL found by Rohrer et al (1999). Additional significant QTL for ovulation rate were found on SSC9 (Cassady et al, 2001), SSC13 and SSC15 (Rathje et al, 1997).…”
Section: Ovulation Ratesupporting
confidence: 53%
“…Five QTL affecting age at puberty have been reported in only two studies (Rohrer et al, 1999;Cassady et al, 2001). Results for ovulation rate are slightly more numerous, as 14 chromosomal regions associated with variations in OR are reported in PiqQTLdb (Rohrer et al, 1999;Wilkie et al, 1999;Cassady et al, 2001;Campbell et al, 2003). Regarding litter size, 12 QTL located on 10 different chromosomes have been reported (Rathje et al, 1997;Cassady et al, 2001;de Koning et al, 2001;Noguera et al, 2006;Tribout et al, 2008), of which only those reported by Noguera et al (2006) reached a genome-wide significance level (P , 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, murine chromosome 5 was shown to be homologous to bovine chromosomes 4, 6, 17, a n d 2 5 , p a r ti c u l a r l y t o c h r o m o s o m e 6 ( h t t p :/ / bos.cvm.tamu.edu). On the other hand, in pigs, QTL studies for reproduction traits including ovulation rate, litter size, and prenatal survival have also been carried out extensively, and many QTLs were identified on swine chromosome 8 [1,3,10,26]. Also, swine chromosome 8 was shown to be homologous to portions of murine chromosome 5 (http:// iowa.thearkdb.org), as well as murine chromosomes 3 and 8.…”
Section: Discussionmentioning
confidence: 99%